50 Drug-eluting balloons and drug-eluting stents in the treatment of small coronary arteries: a systematic review and meta-analysis of long-term clinical outcomes. (6th October 2022) - Murphy, G; Naughton, A; Durand, R; Heron, E; McCaughey, C; Murphy, RT; Pearson, I
Abstract : Introduction: Coronary artery disease is a leading cause of mortality and morbidity worldwide. For those undergoing PCI, there are 20–30% with disease of small coronary arteries. It is often diffuse and multi-vessel and confers higher rates of major adverse cardiac events (MACE) and target lesion failure (TLF) after coronary intervention (2, 3). Best practice guidelines on the management of these small vessel interventions remain limited. Drug-eluting balloons are a novel therapy which have shown promise in treating in-stent restenosis (ISR). However, their use in small coronary arteries compared to drug-eluting stents remains unclear. This systematic review and meta-analysis of randomised controlled trials compare long-term outcomes (>1 year) of drug-eluting balloons (DEB) Vs. Drug-eluting stents (DES) in the treatment of small coronary artery disease (<3mm). Methods: A systematic review was completed within PRISMA guidelines in August 2021. The primary outcome was non-inferiority of DEB Vs. DES in major adverse cardiac events (MACE) amongst RCTs. Secondary outcomes include all-cause mortality, MI, vessel thrombosis, major bleeding, and target vessel revascularisation at one, two, and three years. Two independent reviewers extracted data. All outcomes used the Mantel-Haenszel and Random effect model. Odds ratios (OR) were presented with a 95% confidence interval (CI). Results: Results are illustrated in figure 1 to figure 11 . Of 4661 articles, four RCTs were included (1414 patients). DEB demonstrated reduced rates of non-fatal MI at one year, OR 0.44, (95% CI 0.2, 0.94) ( figure 5 ), and Basket-2 small reported a significant reduction in two-year bleeding rates OR 0.3, (95% CI 0.1, 0.91) ( figure 9 ). DEBs were non-inferior to DES for all other outcomes. MACE 1 Year 2 Year 1 year 2 years MI 1 year 2 years Vessel Thrombosis 1 year Major bleeding 1 year 2 year Target vessel revascularisation 1 year 2 year Conclusion: Long-duration follow-up of DEB and DES use in small coronary arteries demonstrates DEB to be non-inferior to DES in all outcomes across all years of follow-up. There was a significant reduction in rates of non-fatal MI at one year in the DEB arm and a reduction in major bleeding episodes at two years in the Basket Small 2 trial. These data highlight the potential utility and long-term safety of novel DEBs in small coronary artery disease revascularisation.